Multifunctional Thio-Stabilized Gold Nanoparticles for Near-Infrared Fluorescence Detection and Imaging of Activated Caspase-3 - Fan, Jinda; Cheney, Philip P.; Bloch, Sharon; Xu, Baogang; Liang, Kexian; Odonkor, Charles A.; Edwards, Wilson B.; Basak, Soubir; Mintz, Rachel; Biswas, Pratim; Achilefu, Samuel (Current Analytical Chemistry, 2021)
Background: Gold nanoparticles (AuNPs) are commonly used in nanomedicine because of their unique spectral properties, chemical and biological stability, and ability to quench the fluorescence of organic dyes attached to their surfaces. However, the utility of spherical AuNPs for activatable fluorescence sensing of molecular processes have been confined to resonance-matched fluorophores in the 500 nm to 600 nm spectral range to maximize dye fluorescence quenching efficiency. Expanding the repertoire of fluorophore systems into the NIR fluorescence regimen with emission >800 nm will facilitate the analysis of multiple biological events with high detection sensitivity. Objective: The primary goal of this study is to determine if spherical AuNP-induced radiative rate suppression of non-resonant near-infrared (NIR) fluorescent probes can serve as a versatile nanoconstruct for highly sensitive detection and imaging of activated caspase-3 in aqueous media and cancer cells. This required the development of activatable NIR fluorescence sensors of caspase-3 designed to overcome the nonspecific degradation and release of the surface coatings in aqueous media. Methods: We harnessed the fluorescence-quenching properties and multivalency of spherical AuNPs to develop AuNP-templated activatable NIR fluorescent probes to detect activated caspase-3, an intracellular reporter of early cell death. Freshly AuNPs were coated with a multifunctional NIR fluorescent dye-labeled peptide (LS422) consisting of an RGD peptide sequence that targets αvβ3-integrin protein (αvβ3) on the surface of cancer cells to mediate the uptake and internalization of the sensors in tumor cells; a DEVD peptide sequence for reporting the induction of cell death through caspase-3 mediated NIR fluorescence enhancement; and a multidentate hexacysteine sequence for enhancing self-assembly and stabilizing the multifunctional construct on AuNPs. The integrin-binding affinity of LS422 and caspase-3 kinetics were determined by competitive radioligand binding and fluorogenic peptide assays, respectively. Detection of intracellular caspase-3, cell viability, and the internalization of LS422 in cancer cells was determined by confocal NIR fluorescence spectroscopy and microscopy. Results: Narrow size AuNPs (13 nm) were prepared and characterized by transmission electron microscopy and dynamic light scattering. When assembled on the AuNPs, the binding constant of LS422 for αvβ3 improved 11- fold from 13.2 nM to 1.2 nM. Whereas the catalytic turnover of caspase-3 by LS422-AuNPs was similar to the reference fluorogenic peptide, the binding affinity for the enzyme increased by a factor of 2. Unlike the αvβ3 positive, but caspase-3 negative breast cancer MCF-7 cells, treatment of the αvβ3 and caspase-3 positive lung cancer A549 cells with Paclitaxel showed significant fluorescence enhancement within 30 minutes, which correlated with caspase-3 specific activation of LS422-AuNPs fluorescence. The incorporation of a 3.5 mW NIR laser source into our spectrofluorometer increased the detection sensitivity by an order of magnitude (limit of detection 0.1 nM of cypate) and significantly decreased the signal noise relative to a xenon lamp. This gain in sensitivity enabled the detection of substrate hydrolysis at a broad range of inhibitor concentrations without photobleaching the cypate dye. Conclusion: The multifunctional AuNPs demonstrate the use of a non-resonant quenching strategy to design activatable NIR fluorescence molecular probes. The nanoconstruct offers a selective reporting method for detecting activated caspase-3, imaging of cell viability, identifying dying cells, and visualizing the functional status of intracellular enzymes. Performing these tasks with NIR fluorescent probes creates an opportunity to translate the in vitro and cellular analysis of enzymes into in vivo interrogation of their functional status using deep tissue penetrating NIR fluorescence analytical methods.
Keywords: Gold nanoparticles